Is Dry Eye Associated with Acquired Aponeurogenic Blepharoptosis?. (3rd March 2014) - Moesen, Ingemarie; van den Bosch, Willem; Wubbels, René; Paridaens, Dion
Abstract: Purpose : To study the relation between signs of dry eye and acquired aponeurogenic blepharoptosis. Methods : Prospective case-control study in which 100 patients with uni-or bilateral acquired aponeurogenic blepharoptosis were matched for age and gender to 100 controls. The margin-reflex distance (MRD), the Schirmer-1 score, the duration of the tear film break up time (BUT), and the presence of any corneal staining with fluorescein were evaluated in both groups and compared. Data were analysed using either Fisher's exact test or linear regression. Results : The Schirmer-1 score was <10 mm in 36 patients versus 14 controls ( p  = 0.0005). It was <5 mm in 15 patients versus 5 controls ( p  = 0.03). Hard contact lenses were worn by 29 patients versus 4 controls ( p  = 0.000002), and soft contact lenses by 11 patients and 4 controls ( p  = 0.1). After exclusion of contact lens wearers from analysis, the Schirmer-1 score was <10 mm in 30 of the remaining 60 patients and in 17 of the remaining 92 controls ( p  = 0.00006). The tear BUT was <10 sec in 75 patients versus 71 controls ( p  = 0.6). Corneal staining was present in 25 patients versus 15 controls ( p  = 0.1). The score of the Schirmer-1 test and the MRD decreased with age in both groups. Conclusion : (1) Compared to matched controls, patients with acquired aponeurogenic blepharoptosis more often have a decreased aqueous tear production (as measured by a Schirmer-1 test). Although a low tear production may have a causative role in the etiology of acquired blepharoptosis, it may also be explained by a dampened reflex in blepharoptosis patients (2) With age, the MRD as well as the Schirmer-1 score decrease in both groups.